Polymorphisms in immunoregulatory genes and the risk of histologic chorioamnionitis in Caucasoid women: a case control study - Heatley Susan L; Mullighan Charles G; Hart Prue H; Annells Margaret F; Robinson Jeffrey S; McDonald Helen M (BMC, 2005)
Abstract Background Chorioamnionitis is a common underlying cause of preterm birth (PTB). It is hypothesised that polymorphisms in immunoregulatory genes influence the host response to infection and subsequent preterm birth. The relationship between histologic chorioamnionitis and 22 single nucleotide polymorphisms in 11 immunoregulatory genes was examined in a case-control study. Methods Placentas of 181 Caucasoid women with spontaneous PTB prior to 35 weeks were examined for histologic chorioamnionitis. Polymorphisms in genes IL1A, IL1B, IL1RN, IL1R1, tumour necrosis factor (TNF), IL4, IL6, IL10, transforming growth factor beta-1 (TGFB1), Fas (TNFRSF6), and mannose-binding lectin (MBL2) were genotyped by polymerase chain reaction and sequence specific primers. Multivariable logistic regression including demographic and genetic variables and Kaplan-Meier survival analyses of genotype frequencies and pregnancy outcome were performed. Results Sixty-nine (34%) women had histologic evidence of acute chorioamnionitis. Carriage of the IL10-1082A/-819T/592A (ATA) haplotype [Multivariable Odds ratio (MOR) 1.9, P = 0.05] and MBL2 codon 54Asp allele (MOR 2.0, P = 0.04), were positively associated with chorioamnionitis, while the TNFRSF6-1377A/-670G (AG) haplotype (MOR 0.4, P = 0.03) and homozygosity for TGFB1-800G/509T (GT) haplotype (MOR 0.2, P = 0.04) were negatively associated. Conclusion These findings demonstrate that polymorphisms in immunoregulatory genes IL10, MBL2, TNFRSF6 and TGFB1 may influence susceptibility to chorioamnionitis.